Automatic Text Summarization and Entity Extraction from Meeting Minutes - Ryan D’silva , Anushka Paradkar (International Journal of Advanced Science and Technology, 2020)
An end-to-end solution that would record the meeting and generate a concise summary/minutes. The application would facilitate the generation of minutes using recorded audio or scanned documents through a technique using extractive and abstractive summarization while also picking out important entities from the text using named entity recognition. Identifying different speakers in the audio is also a secondary objective.